PELATIHAN BIMBINGAN BACA UNTUK MENINGKATKAN MINAT BACA PADA ANAK USIA DINI DI TP. MELATI C DESA CIREUNGHAS - Sopiati, Sopiati; Hidayat, Ade Ruslan (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
Increasing the reading interest of early childhood is a crucial aspect in the development of character and academic abilities. In TP. Melati C Desa Cireunghas, many children lack a strong reading interest, thus necessitating a reading training program to enhance their reading skills and interest. In the reading guidance training program at TP. Melati C Desa Cireunghas, the method of Participatory Action Research (PAR) can be used to increase early childhood reading interest more effectively. The community, including parents, teachers, and children, actively participate in the planning, implementation, and evaluation of the reading training program. This allows them to understand the needs and challenges faced by children in improving their reading abilities. The outcomes of the reading training program include increased self-confidence and motivation among students to read more actively. Additionally, the program enhances children's reading skills and increases the school library's book collection. The program also focuses on support, motivation, lectures, and discussions. The reading guidance training program at TP. Melati C Desa Cireunghas has successfully increased the reading interest and abilities of early childhood children. With an effective community service method, this program can serve as a good example for other schools to enhance children's academic abilities.